2020
DOI: 10.20473/j.djmkg.v53.i1.p50-56
|View full text |Cite
|
Sign up to set email alerts
|

Simple smartphone applications for superimposing 3D imagery in forensic dentistry

Abstract: Background: Forensic dentistry identification commonly involves using dental cast models as ante-mortem data. Here, dentists generally send the pictures as well as the dental records. However, in recent times, dentists – especially orthodontists and prosthodontists – are using 3D scanners in view of reducing the space for cast model storage as well as sending the 3D imaging for fabricating clear aligners and other items such as crowns and bridges. This new trend means data transmission and viewing has become m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…13,15,17,18 The development of a selfie identification application and other smartphone applications for 3-D image superimposition in FO has also centred selfies in recent days. 16,29 Digital software with features that allow photo editing and quantification with the evaluation of dental traits may aid in human identification. 23 Additionally, performing a general craniofacial assessment on the photographs provided, superimposition discretional, before continuing with a more detailed dental analysis may prove beneficial and considered more thorough.…”
Section: Discussionmentioning
confidence: 99%
“…13,15,17,18 The development of a selfie identification application and other smartphone applications for 3-D image superimposition in FO has also centred selfies in recent days. 16,29 Digital software with features that allow photo editing and quantification with the evaluation of dental traits may aid in human identification. 23 Additionally, performing a general craniofacial assessment on the photographs provided, superimposition discretional, before continuing with a more detailed dental analysis may prove beneficial and considered more thorough.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this method provides fast and simple image capture and processing without radiation exposure to the subjects. A study by Utomo et al [27] found that using a smartphone and its application, such as CAD Assistant, Exocade, and Adobe Photoshop Mix, is a suitable method for superimposing 3D models.…”
Section: Imaging Technique For Bitemark Analysismentioning
confidence: 99%
“…In terms of performance, it may not meet certain industry's special requirements for the functional performance of a certain module. For example, the clothing industry [2] that draws clothes sketches in the 2D environment often needs to evaluate their effects in the 3D environment, and general CAD software does not provide the transformation function that requires clothing expertise; the criminal investigation industry [3] uses mobile devices to collect On-site evidence, which requires CAD software to provide the conversion interface of special instrument data, the compatibility of different hardware data, and the standardized rendering of graphics data. Therefore, the current general CAD software still needs improvement.…”
Section: General Cad Softwarementioning
confidence: 99%